2006
DOI: 10.1289/ehp.9081
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Airborne Particulate Matter and Adverse Perinatal Outcomes: A Biologically Plausible Mechanistic Framework for Exploring Potential Effect Modification by Nutrition

Abstract: ObjectivesThe specific objectives are threefold: to describe the biologically plausible mechanistic pathways by which exposure to particulate matter (PM) may lead to the adverse perinatal outcomes of low birth weight (LBW), intrauterine growth retardation (IUGR), and preterm delivery (PTD); review the evidence showing that nutrition affects the biologic pathways; and explain the mechanisms by which nutrition may modify the impact of PM exposure on perinatal outcomes.MethodsWe propose an interdisciplinary conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
297
1
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(314 citation statements)
references
References 114 publications
(149 reference statements)
2
297
1
14
Order By: Relevance
“…Although in a previous review study it was concluded that PM 10 had an effect on LBW [22], we found no significant association in this regard. The postulated mechanism for the effect of PM 10 is that PM 10 may bind to placental growth factor resulted in decreased fetal-placental exchange of oxygen and nutrients, nutrient and oxygen supply during gestation are key factors regulating fetal growth rate [23]. If this is true, a probable justification for this contrasting result is that there would necessarily be a threshold effect [8], but in our study the level of exposure to PM 10 may have been under the threshold level.…”
Section: Discussionmentioning
confidence: 67%
“…Although in a previous review study it was concluded that PM 10 had an effect on LBW [22], we found no significant association in this regard. The postulated mechanism for the effect of PM 10 is that PM 10 may bind to placental growth factor resulted in decreased fetal-placental exchange of oxygen and nutrients, nutrient and oxygen supply during gestation are key factors regulating fetal growth rate [23]. If this is true, a probable justification for this contrasting result is that there would necessarily be a threshold effect [8], but in our study the level of exposure to PM 10 may have been under the threshold level.…”
Section: Discussionmentioning
confidence: 67%
“…Meanwhile, our findings disagree with those of Medeiros & Gouveia 8 and Bell et al 14 . Kannan et al 19 propose mechanisms resulting in low birth weight due to exposure to PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of DNA adducts have been found in the blood (Perera FP et al, 1992;Petruzzelli S et al, 1998) and placentas (Topinka J et al, 1997) of subjects living in polluted areas, and were also found to be related to birthweight . Maternal nutrition status can be acting as a effect modifier between exposures to airborne particulate matter and adverse perinatal outcomes (Kannan et al, 2006). Maternal pulmonary function has been linked to altered placental vascular function and growth retardation in asthmatic pregnancies (Bracken et al 2003;Clifton et al 2001;Schatz et al 1990).…”
Section: Socioeconomic Status(ses): Health Disparitymentioning
confidence: 99%